URGENSI STRATEGI PEMBELAJARAN BERBASIS PENGALAMAN DALAM PEMBELAJARAN PENDIDIKAN SEJARAH - Krisna Aji, Satria; Fahruddin (Universitas Negeri Semarang, 2025)
Experience-based learning strategies are a relevant innovative approach in history education because they are able to provide more contextual and meaningful learning experiences. This article aims to explore the urgency of implementing experience-based learning strategies in history learning. This research uses descriptive qualitative methods with a case study approach in high schools in the Yogyakarta area. Data was obtained through observation, interviews with history teachers, and document analysis. The research results show that experience-based learning strategies, such as simulations, visits to historical sites, and collaborative projects, are able to increase students' interest in learning, understanding of history, and strengthening character values ​​such as nationalism and empathy. However, the implementation of this strategy still faces several obstacles, such as limited facilities, time and policy support. This article emphasizes the importance of support from educational institutions in providing facilities and teacher training to optimize experience-based strategies. By implementing this strategy effectively, history learning not only focuses on transferring knowledge, but is also able to build student involvement and increase their awareness of the importance of history in today's life.